Understanding animal-oriented social media collaboration in Australia’s 2019–20 bushfire crisis - Karhu, Mari; Rantasila, Anna; Olsson, Thomas; Häkkilä, Jonna (Frontiers in Communication, 2024)
In the past decade, social media has served as a vehicle for sharing information and coordinating actions during sudden crises. However, much of the research has focused on local communities directly affected by crisis and the human recipients of aid. This paper explores a case where handicraft makers across the globe collaborated on social media – namely Facebook – to help Australian wildlife during the 2019–20 bushfire crisis. Based on 12 semi-structured interviews, we report how animal-centered visual content spread through a broader hybrid media system, arousing emotions that played a crucial role in increasing awareness of the crisis and catalyzing action. The findings highlight how participants actively sought possibilities for utilizing their knowledge and expertise within the project and experienced receiving immaterial rewards and benefits as compensation for their efforts. The findings also show how participants had various roles in the collaborative initiative – alternating between online and offline environments. However, the ongoing crisis coupled with the related pressure and stress, the rapidly increasing number of helpers, communication ambiguities, and technological challenges, led to chaos, heightened emotions, and fueled dissension within the group. These factors posed challenges to collaboration, further highlighting the negative and toxic communication cultures of social media. This paper enriches our understanding of how social media can enable, but also challenge, bottom-up community-driven, animal-oriented solidarity actions and long-distance crisis collaboration.